Data on genome resequencing of pigmented and non-pigmented Malaysian rice varieties - Zainal-Abidin, Rabiatul-Adawiah (Data Brief, 2020)
The genomics and genetic data of pigmented and non-pigmented Malaysian rice varieties are still limited. Hence, we performed the genome resequencing of two black rice varieties (Bali, Pulut Hitam 9), two red rice varieties (MRM16, MRQ100) and two white rice varieties (MR297 and MRQ76) using Illumina HiSeq 4000 platform with 30x sequencing coverage. We aimed to identify and annotate single nucleotide polymorphisms (SNPs) from the genome of these four pigmented and two non-pigmented rice varieties. The potential SNPs will be used in developing the functional SNP markers related to nutritional (i.e. antioxidant, folate, amylose) and quality (i.e. aromatic) traits. Raw data of the pigmented and non-pigmented rice varieties have been deposited into the European Nucleotide Archive (ENA) database with accession number PRJEB29070 and PRJEB32344, respectively.